2020
DOI: 10.1111/jfr3.12620
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of potential flood hazard area using GIS‐based multi‐criteria analysis and satellite data‐derived water index

Abstract: This article identifies potential flood hazard areas through multi-criteria analysis in Allahabad district, India. The study has incorporated eight criteria, namely, flow accumulation, draining capability, elevation, groundwater depth, land use, runoff coefficient, slope, and geology for preparing hazard index. The weights of the criteria were obtained through the analytical hierarchy process (AHP) method based on their relative importance for occurring floods. Finally, a flood hazard index (FHI) was prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 47 publications
2
51
0
2
Order By: Relevance
“…Geology has the lowest weight, and this may be due the steep nature of the area, where water drains very fast toward the sea and hence has a low chance of percolating down. A study by Dash and Sar (2020) also concluded that geology is the least significant factor in flood generation. The weights of the factors and sub-factors (Table 9) were used to generate the potential flood map.…”
Section: Land Use Classification Accuracymentioning
confidence: 98%
See 1 more Smart Citation
“…Geology has the lowest weight, and this may be due the steep nature of the area, where water drains very fast toward the sea and hence has a low chance of percolating down. A study by Dash and Sar (2020) also concluded that geology is the least significant factor in flood generation. The weights of the factors and sub-factors (Table 9) were used to generate the potential flood map.…”
Section: Land Use Classification Accuracymentioning
confidence: 98%
“…Due to these advantages, AHP is used in GIS to improve decision-making processes (Estoque 2012;Samanta et al 2016). Substantial research has been conducted on the combination of AHP and GIS for flood studies (Dash and Sar 2020;Kazakis et al 2015;Ouma and Tateishi 2014;Papaioannou et al 2015;Stefanidis and Stathis 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Following a detailed analysis of each region, we found that the most researched areas were: the United States, representing 13.19% of the total articles analyzed and 71.72% of the articles located in North America [47][48][49]; the United Kingdom, with 90 articles representing 17.92% of the articles in Europe and 6.78% of the total papers [50][51][52]; Italy and Spain, accounting for 5.27% of the entire articles and 13.94% of the scientific papers published in Europe, respectively [53][54][55]; and China, accounting for 5.27% of the total articles and 20.11% of the articles in Asia [56][57][58]. A significant percentage of publications also came from India, representing 16.6% of all Asian scientific articles and 4.37% of the total publications [59][60][61]. The latest analysis of publications showed us that the papers that have China and India as their study area are increasingly numerous.…”
Section: Spatial Distribution Of Researchmentioning
confidence: 99%
“…Flow accumulation is considered a relevant parameter of water logging which defines the cumulative flow downslope as well as reflects the ability to drain out excess rain water (Dash and Sar, 2020). As a significant part of the low-lying area within municipality is waterlogged due to insufficiency in water outflow, a raster flow accumulation map (Fig.…”
Section: Flow Accumulationmentioning
confidence: 99%
“…Being a quasi-natural manifestation of lowlands, flood and water logging are observed throughout the country (Bowonder et 30 al., 1986) viz. Uttar Pradesh (Dwivedi, 1994); (Dash and Sar, 2020); Andhra Pradesh (Choubey, 1998); Gangetic West Bengal (Sanyal and Lu, 2005); (Sanyal and Lu, 2006); Indo Gangetic plain (Pandey et al, 2010); Karnataka, India (Ritzema et al, 2008); as well as the developing world Jiangsu, China (Huang et al, 2018); Ethiopia (Getahun and Gebre, 2015) and therefore is regarded as a global issue. Moreover, floods in urban areas intensify with the increase of impervious surfaces, which eventually cause changes in run-off conveyance network (Dewan, 2013).…”
Section: Introductionmentioning
confidence: 99%